Nggoli Weaving Marketing Strategy in An Effort to Increase People’s Income in Sangga Village Lambu Sub District, Bima District - Wulandari, Putri; Akib, Haedar; Aslinda, Aslinda (Universitas Negeri Makassar, 2025)
This study aims to find out the marketing strategy as well as the inhibiting factors and supporting factors for the nggoli weaving business in Sangga village, Lambu district, Bima district. This type of research is descriptive qualitative research. Data collection techniques in this study through observation, interviews, and documentation. The data analysis technique in this study uses condensation data, data presentation, and draws conclusions. The results of this study indicate that the marketing strategy applied is directed and maximized by determining segmentation, targeting, positioning. Another marketing strategy used is the marketing mix which includes product, price, place and promotion. The inhibiting factors are the lack of promotional activities through social media, not having special packaging, not being creative in marketing products and supporting factors consisting of manual weaving processes, various products produced, affordable prices and availability of local goods.Keyword : Marketing Strategy, Nggoli Weaving, Community Income